MULTIMODAL IMAGING OF MOSAIC RETINOPATHY IN CARRIERS OF HEREDITARY X-LINKED RECESSIVE DISEASES. Issue 5 (May 2018) - Wu, An-Lun; Wang, Jung-Pan; Tseng, Yun-Ju; Liu, Laura; Kang, Yu-Chuan; Chen, Kuan-Jen; Chao, An-Ning; Yeh, Lung-Kun; Chen, Tun-Lu; Hwang, Yih-Shiou; Wu, Wei-Chi; Lai, Chi-Chun; et al.
Abstract : Purpose: To investigate the clinical features in carriers of X-linked retinitis pigmentosa, X-linked ocular albinism, and choroideremia (CHM) using multimodal imaging and to assess their diagnostic value in these three mosaic retinopathies. Methods: We prospectively examined 14 carriers of 3 X-linked recessive disorders (X-linked retinitis pigmentosa, X-linked ocular albinism, and CHM). Details of abnormalities of retinal morphology were evaluated using fundus photography, fundus autofluorescence (FAF) imaging, and spectral domain optical coherence tomography. Results: In six X-linked retinitis pigmentosa carriers, fundus appearance varied from unremarkable to the presence of tapetal-like reflex and pigmentary changes. On FAF imaging, all carriers exhibited a bright radial reflex against a dark background. By spectral domain optical coherence tomography, loss of the ellipsoid zone in the macula was observed in 3 carriers (50%). Regarding the retinal laminar architecture, 4 carriers (66.7%) showed thinning of the outer nuclear layer and a dentate appearance of the outer plexiform layer. All five X-linked ocular albinism carriers showed a characteristic mud-splatter patterned fundus, dark radial streaks against a bright background on FAF imaging, and a normal-appearing retinal structure by spectral domain optical coherence tomography imaging. Two of the 3 CHM carriers (66.7%) showed a diffuse moth-eaten appearance of the fundus, and all 3 showed irregular hyper-FAF and hypo-FAF spots throughout the affected area. In the CHM carriers, the structural changes observed by spectral domain optical coherence tomography imaging were variable. Conclusion: Our findings in an Asian cohort suggest that FAF imaging is a practical diagnostic test for differentiating X-linked retinitis pigmentosa, X-linked ocular albinism, and CHM carriers. Wide-field FAF is an easy and helpful adjunct to testing for the correct diagnosis and identification of lyonization in carriers of these three mosaic retinopathies. Abstract : Supplemental Digital Content is Available in the Text.Fundus autofluorescence imaging is the most valuable technique for diagnosis and for differentiating carriers of X-linked retinitis pigmentosa, X-linked ocular albinism, and choroideremia in an Asian cohort presented with mosaic retinopathy.